2018
DOI: 10.4067/s0718-221x2018005041101
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes de la satisfacción laboral en la industria de la madera y el papel: estudio en españa y hallazgos en otros países

Abstract: Esta investigación se desarrolla en el colectivo de trabajadores ocupados pertenecientes a la cosecha forestal, industria de la madera y papel, y su comparación con el total nacional. El ámbito es el mercado laboral español. Se escogen 14 variables cuantitativas, extraídas de la Encuesta de calidad de vida en el trabajo (Ministerio Empleo y Seguridad Social). El objetivo primero es averiguar qué variables y agrupaciones de variables (o factores) afectan a la satisfacción laboral en el sector forestal, madera y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Studies [42][43][44][45] have shown that salary, promotion, bonuses, and other types of rewards are used by most enterprises to improve employee performance. Praise, setting realistic and achievable goals, appropriate workload definition, employee engagement, appropriate empowerment, responsibility, feedback, work equipment, expressing the positive personality features of a supervisor, appropriate leadership style, correctness by senior staff and company, and providing relevant information are considered to be other important motivation factors [46][47][48][49][50][51][52][53][54].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies [42][43][44][45] have shown that salary, promotion, bonuses, and other types of rewards are used by most enterprises to improve employee performance. Praise, setting realistic and achievable goals, appropriate workload definition, employee engagement, appropriate empowerment, responsibility, feedback, work equipment, expressing the positive personality features of a supervisor, appropriate leadership style, correctness by senior staff and company, and providing relevant information are considered to be other important motivation factors [46][47][48][49][50][51][52][53][54].…”
Section: Literature Reviewmentioning
confidence: 99%
“…La estabilidad económica influye positivamente en las condiciones laborales en tiempos de pandemia de los colaboradores del sector del calzado en Guanajuato. Resultados respaldados en la literatura en condiciones normales (Casas, Repullo, Lorenzo y Cañas, 2002;Castillo, Goya, Romero y Tipan, 2020;Limaymanta y Turpo-Gebera, 2021;Sánchez-Sellero, 2021;Sánchez-Sellero y Sánchez-Sellero, 2018). Además, los resultados, hacen visible el aspecto económico de los colaboradores del sector calzado de esta región, al expresar que su nivel de vida, estabilidad económica, salario y prestaciones es regular (más del 70% en cada factor), revelando la situación precarizada que están viviendo los que laboran en este sector.…”
Section: Discussionunclassified